Rural Education: Impacts of nucleation and school transportation on guaranteed access to education - Enildo Chaves Caldas; Eraldo Souza do Carmo (Revista Brasileira de Educação do Campo)
This article examines rural education in Brazil, highlighting the difficulties faced due to inadequate infrastructure and a lack of resources, which affect the quality of education. The aim was to understand how public policy on school transportation in Pará has been portrayed in the literature. The methodology is qualitative, with an emphasis on document analysis of norms and policies related to school transportation, with a time frame between 2009 and 2023. Relevant dissertations and documents were analyzed in order to identify gaps and challenges in the implementation of public policies. The study reveals that, despite the Caminho da Escola and PNATE programs, there are inequalities in the distribution of resources and persistent problems in transport infrastructure, such as scrapping of vehicles, lack of logistics on the route and compliance with legislation. In view of this, we highlight the need for a collaborative approach to ensure educational equality in all localities in the state of Pará.